“O Nga: Laa” sebagai Wujud Akuntabilitas Biaya Pernikahan - Mohamad Anwar Thalib (Jurnal Riset dan Aplikasi: Akuntansi dan Manajemen, 2023)
This study aims to formulate a form of accountability for the cost of marriage on the part of women in Gorontalo. This research uses spiritual paradigm. The approach used is the Islamic ethnometodology. The results found that a sense of kinship is the accountability practices beginning for marriage costs. This sense constructs cost accountability practice by thinking of using costs, covering the lack of costs, beautifying, and showing the wedding situation. These actions are driven by spirits of trust, kinship, respect, and mutual trust. This spirits live by the gift of kinship given by God.